Caracterização molecular de isolados de Toxoplasma gondii obtidos de crianças com toxoplasmose congênita no Estado de Minas Gerais - Ana Carolina de Aguiar Vasconcelos Carneiro (2011)
Toxoplasma gondii is a widely distributed Apicomplexa parasite with great medical importance. Congenital toxoplasmosis has been associated with abortion and stillborn, debility and neonatal mortality. Toxoplasmosis can be diagnosed through serologic methods or by directed methods: parasite isolation in mice (bioassay) or Polimerase Chain Reaction assay (PCR). The Programa Estadual de Triagem Neonatal (Neonatal Screening State Program) in Minas Gerais state, evaluated 146.307 children by anti-T. gondii IgM antibodies search, using blood samples dried in filter paper. Out of those, 220 newborns presented positive/doubtful results and were selected for this study. New blood samples were collected from newborns for PCR and bioassay. Toxoplasmosis was confirmed in 178 children who had specific IgG antibodies after 12 months. The B1 gene amplification by nested PCR was performed on all 220 blood samples. Sixty-four (29,1%) children presented positive results by PCR (31,46% sensibility and 80,95% specificity). This PCR in peripheral blood was not sufficiently sensitive or specific to be considered as an useful tool for the diagnosis of congenital toxoplasmosis in newborns. Using bioassay in mice, 27 T. gondii isolates were obtained. Parasitemia was detected in 15,2% (27/178) ofnewborns with congenital toxoplasmosis. T. gondii isolates were divided into three different groups according to the virulence in mice: Fourteen isolates (54%) were characterized as intermediate virulence, ten (38%) as virulent and only two (8%) as avirulent isolates. The genetic variability was assessed by Restricted Fragment Length Polymorphism (PCR-RFLP) in 11 loci (SAG1, 5+3SAG2, SAG2 alt, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, Apico). The strains RH (Type I), ME49 (Type II) and VEG (Type III) were used as references strains. The complete genotyping was achieved in 25/27 isolates (92,6%). Fourteen different genotypes were identified: two previously described genotypes, common in Brazil (BrII and BrIII) and twelve new genotypes. One isolate presented mixed infection. No archetypal I, II or III genotype were found in the isolates studied. It was not observed association between clinical signs of congenital toxoplasmosis and the results obtained by molecular diagnosis, bioassay, virulence or genotyping of the isolates. This is the first report of isolation and genotyping of T. gondii from newborns blood in Brazil and confirms the genotypic variability of the parasites in our country.